A national Israeli survey of neuraxial anesthesia for cesarean delivery: pre-operative block assessment and intra-operative pain management. (May 2022) - Orbach-Zinger, S.; Grant, T.G.; Zahalka, M.; Ioscovich, A.; Fein, S.; Ginosar, Y.; Matkovski, O.; Weiniger, C.F.; Binyamin, Y.
Highlights: A national Israeli survey on anesthesia for cesarean delivery was performed. Block assessment and intra-operative pain management during surgery were assessed. Response rate was 81.1% Large variations in neuraxial anesthesia regimens exist. Large variations in block assessment technique exist. Abstract: Background: Neuraxial protocols for cesarean delivery differ among institutions, with various means of assessing the block prior to incision and managing breakthrough intra-operative pain. The different approaches used to deal with these issues in Israel have not been assessed. Methods: Questionnaires were distributed to all anesthesiologists working in obstetric units in Israeli hospitals. The survey included several non-identifying respondent details intended to allow a description of the study population as a whole and multiple-choice questions addressing neuraxial techniques, method of pre-operative block assessment and medications used to treat intra-operative pain. Results: Three hundred and sixty-one doctors completed the survey in 24 medical centers, an 81.1% response rate. Thirteen different protocols for spinal anesthesia and 20 different protocols for epidural anesthesia were described. Nine different protocols for assessment of the block prior to incision were identified, with significant inter-institutional differences ( P <0.001). For treatment of intra-operative pain prior to delivery, 35.7% of spinals given and 40% of epidurals given were converted to general anesthesia whereas, after delivery, conversion of spinal to general anesthesia was 18% and epidural to general anesthesia was 18.6%. Conclusions: There were a variety of spinal and epidural regimens used as well as different methods for assessing the block and managing intra-operative pain. Further studies should be performed to identify optimal techniques for neuraxial anesthesia for pre-operative block assessment and for management of intra-operative pain.